Interaction Between VO₂max and Sportpersonship: A Study on Middle-Distance Athletes of the Sportyjoy Club (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to identify the relationship between VO₂max, as an indicator of aerobic capacity, and sportpersonship, as a measure of sports participation orientation, among middle-distance runners of the Sportyjoy Club. The method used was a quantitative correlational approach with 10 study subjects selected through purposive sampling. VO₂max was measured using the Cooper 2.4 km run test, while sportpersonship was assessed using the Sports Participation Model Questionnaire (SPMQ). Data analysis employed descriptive statistics and Pearson correlation tests. The results showed that the average VO₂max of male participants (44.24 ± 6.59 ml/kg/min) was higher than that of female participants (41.92 ± 5.64 ml/kg/min). However, no significant linear relationship was found between VO₂max and sportpersonship (r = -0.076, p = 0.836). These findings indicate that VO₂max is not a primary predictor of sportpersonship among middle-distance athletes. It is recommended that training programs adopt a holistic approach encompassing both physical and mental aspects of athletes to comprehensively develop sportpersonship.